Healthcare Access of Autistic Language Minorities: The Case of English Official Language Minorities in Quebec, Canada - Amantayev, Nariman; Rao, Sabrina; Nadig, Aparna (Minorités linguistiques et société, 2025)
Abstract English and French are both official languages in Canada. Whereas official language minorities (English speakers in Quebec, French speakers in the rest of Canada) face healthcare barriers and poor health outcomes, autistic individuals and their families also struggle with accessing healthcare. We examined healthcare access at the intersection of these groups: the autistic community, including English minority-language speakers from Quebec, French majority-language speakers from Quebec, and English majority-language speakers from elsewhere in Canada (n = 165). Linguistic minorities reported poorer access to publicly-funded services and lower satisfaction that their language needs were being met than did linguistic majorities. Foreign-born English speakers also experienced poorer access than their Canadian-born counterparts. These preliminary findings suggest that autistic language minorities face known barriers to accessing healthcare, potentially at a higher rate than that experienced by language minorities in general. Résumé L’anglais et le français sont les langues officielles du Canada. Les minorités de langue officielle (anglophones au Québec, francophones hors Québec) font face à des obstacles en matière de santé, tout comme les personnes autistes et leurs familles. Nous avons examiné l’accès aux services de santé à l’intersection de ces groupes : la communauté autiste, incluant des anglophones (minoritaires) et francophones (majoritaires) du Québec, ainsi que des anglophones (majoritaires) du reste du Canada (n = 165). Les minorités linguistiques déclarent un accès plus difficile aux services de santé publics et une moindre satisfaction quant à la prise en compte de leurs besoins linguistiques, comparativement aux majorités linguistiques. Les anglophones nés à l’étranger rapportent également un accès plus difficile que leurs pairs nés au Canada. Ces résultats préliminaires suggèrent que les minorités linguistiques autistes font face à des obstacles connus en matière d’accès aux soins, possiblement à un degré plus élevé.

Language related difficulties experienced by caregivers of English-speaking seniors in Quebec - Sanderson, Duncan (SAGE Open, 2020)
Little research has examined communication problems between speakers of official minority languages (patients or caregivers) and health care providers. The objective of this research was to identify the types of issues experienced by English-speaking caregivers of seniors in Quebec, as they interact with French-speaking health care providers. The majority of the caregivers interviewed indicated that they were satisfied with physicians’ interaction with the seniors they cared for. However, problems included health care providers who do not or who refuse to speak English, hospice personnel with insufficient English, anxiety about speaking to personnel in French, traveling to receive services in English, acting as an informal interpreter, receiving written documents in French, scheduling appointments through French-only phone systems or receptionists, and discrimination. The main finding is that in Quebec, language asymmetry might create additional stresses for an English-speaking caregiver, who is already likely to be stressed because of their caregiver role.